Downtime Distribution for Analyzing Inflow and Outflow of Water in Mettur Dam - Aparna, T.; kumar, P. Senthil (International Journal of Psychosocial Rehabilitation, 2020)
Agriculture is completely based on irrigation and water as the output factor for food production .Large Dams plays a major role in lifting up the economic and social development of a country. The inflow and outflow of water from Dam plays a predominant role in the agriculture sector. In this paper we inspect the inflow and outflow of water in Mettur Dam during June 2008-May 2009, mathematically we fit the downtime distribution in terms of Laplace transforms (LT) and predicted the Laplace transforms is inverted numerically. Some properties of downtime distributions have also been reviewed.